Analysis The Impact of The Coastal Protection Construction Development Plan On Shoreline and Estuary Changes - Teuku Mudi Hafli; Fasdarsyah Fasdarsyah1; Ninda Nidya; David Sarana; Syibral Syibral (LPPM Universitas Malikussaleh, 2022)
This beach, which is located in Aceh Province, especially Bireuen Regency, Jangka District, Kuala Ceurape, is an tourist beach area, aquaculture,e and also a settlement. Several efforts to control sedimentation and erosion have been carried out by constructing coastal protection buildings on the coast. However, in the estuary, there are no coastal protection structures such as jetties. Estuaries have quite high economic value because they function as connecting channels between sea and land. The height of the wave currents around the estuary can cause the accumulation of sediment or silt of the beach by erosion which can result in decreased utilization of the coast around the estuary. Therefore, it is necessary to analyze the impact of coastal protection construction planning to determine the formation of sedimentation and erosion that occurs around the coast. This study used the Delft3D application to simulate changes in coastlines and estuaries over a period of 5 years. The data used in this study are wind data for 10 years from 2012 to 2021, depth data, tidal component data, factor morphology calculations, significant wave height calculations (Hs,), and significant wave periods (Ts). This simulation uses 4 (four) wind directions, namely North, Northeast, East, and Northwest directions. The results of modeling simulations over a period of 5 years show that the beach condition with the planned construction of the coastal protection has progressed along the coastline by ± 77,053 meters and progress of around ± 77.421 meters on the coast. On the contrary, it experienced a coastline retreat of ± 143.076 meters and experienced a shoreline advance of around ± 84.647 meters in the estuary. So it can be concluded that the construction of the Jetty building alone is not enough to reduce the occurrence of erosion and sedimentation problems around the coast, especially in the estuary. There is a need for the construction of other coastal protection structures.